2002
DOI: 10.1038/sj.ejcn.1601302
|View full text |Cite
|
Sign up to set email alerts
|

Energy intake and expenditure of free-living, lactating Colombian women in an urban setting

Abstract: Objectives:To examine the components of energy balance during lactation in a population of economically disadvantaged women in an urban developing country setting in order to better understand the metabolic response to lactation. Design. Cross-sectional comparison of lactating (LACT) and non-pregnant non-lactating (NPNL) women. Body size and composition were assessed via anthropometry, energy intake was measured using estimated diet records and energy expenditure using indirect calorimetry and the Flex-Heart R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
(44 reference statements)
2
18
0
Order By: Relevance
“…These results are not surprising considering our life history pattern and consequent flexibility in meeting the energy costs of lactation and are comparable to the variation found in other studies of lactational energetics (Butte et al, 1997;Dufour et al, 2002;Goldberg et al, 1991;Guillermo-Tuazon et al, 1992;Panter-Brick, 1993;Sadurskis et al, 1988;Schutz et al, 1980;Singh et al, 1989;van Raaij et al, 1991;Vinoy et al, 2000). However, unlike other studies of lactational energetics, this paper focused on intra-population variation in energetic strategies and the factors that influenced it.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results are not surprising considering our life history pattern and consequent flexibility in meeting the energy costs of lactation and are comparable to the variation found in other studies of lactational energetics (Butte et al, 1997;Dufour et al, 2002;Goldberg et al, 1991;Guillermo-Tuazon et al, 1992;Panter-Brick, 1993;Sadurskis et al, 1988;Schutz et al, 1980;Singh et al, 1989;van Raaij et al, 1991;Vinoy et al, 2000). However, unlike other studies of lactational energetics, this paper focused on intra-population variation in energetic strategies and the factors that influenced it.…”
Section: Discussionsupporting
confidence: 87%
“…The greatest variation in dietary intake was observed among rural Amazonian women (Piperata and Dufour, 2007) and the least was found among a sample of British women (Goldberg et al, 1991). Variation in energy expenditure was highest among poor, urban women living on the outskirts of Cali, Colombia (Dufour et al, 2002), while the least amount of variation was found among a sample of women from the Netherlands (van Raaij et al, 1991). In general, greater variation was observed among women in rural and urban settings in developing countries.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Of those that have, most are focused on women in developed countries (Brewer et al, 1989;Butte et al, 1999;Forsum et al, 1992;Goldberg et al, 1991;Sadurskis et al, 1988;van Raaij et al, 1991) or among women in urban settings in developing nations (Dufour et al, 2002;Madhavapeddi and Roa, 1992;Piers et al, 1995). Generally, these studies have shown that women in urban and (or) more affluent conditions tend to meet their additional energy needs by increasing their dietary energy intakes.…”
mentioning
confidence: 99%